1985
DOI: 10.1037/0022-3514.48.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in group task performance.

Abstract: This research assessed whether males and females differ in their group task performance. Participants worked individually or in three-person same-sex groups on a production task, which required the generation of ideas, or on a discussion task, which required group members to reach consensus concerning their evaluation of an issue. Because the content of the tasks was carefully selected not to favor the interests and expertise of one sex over the other, no sex differences were expected when subjects worked indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 32 publications
0
56
0
Order By: Relevance
“…extent that the combination and integration of a variety of ideas facilitates group creativity, women's tendency to engage in positive interpersonal behaviors should be associated with higher levels of creativity compared with groups composed of men (Wood 1987). Providing some initial support for this line of reasoning, Wood et al (1985) found that groups composed entirely of women generated more creative solutions to a set of three problems than groups composed entirely of men. In addition, Woolley et al (2010) found that the proportion of women in a group significantly correlated with the group's collective intelligence-a strong predictor of group performance across a variety of domains, including creativity.…”
Section: The Effects Of Intergroup Competition On Group Creativity: Smentioning
confidence: 92%
See 1 more Smart Citation
“…extent that the combination and integration of a variety of ideas facilitates group creativity, women's tendency to engage in positive interpersonal behaviors should be associated with higher levels of creativity compared with groups composed of men (Wood 1987). Providing some initial support for this line of reasoning, Wood et al (1985) found that groups composed entirely of women generated more creative solutions to a set of three problems than groups composed entirely of men. In addition, Woolley et al (2010) found that the proportion of women in a group significantly correlated with the group's collective intelligence-a strong predictor of group performance across a variety of domains, including creativity.…”
Section: The Effects Of Intergroup Competition On Group Creativity: Smentioning
confidence: 92%
“…The logic that the interactive effects of intergroup competition and sex composition on creativity largely operate through collaboration implies that this variable may serve to mediate the effects hypothesized in this study (Wood 1987, Wood et al 1985. Thus, we also hypothesize the following.…”
Section: The Effects Of Intergroup Competition On Group Creativity: Smentioning
confidence: 95%
“…The basis of most of the studies cited in the paper includes either the principal agent theory or stakeholder theory, or the combination stakeholder agency theory (Hill & Jones, 1992;Laplume, Sonpar, & Litz, 2008). Various results of gender differences on boards have been reported: more effective communication capabilities (Wood, Polek, & Aiken, 1985), increased incentives to ask critical questions (Konrad, Kramer, & Erkut, 2008), and better group thinking (Wood et al, 1985). Various results of gender differences on boards have been reported: more effective communication capabilities (Wood, Polek, & Aiken, 1985), increased incentives to ask critical questions (Konrad, Kramer, & Erkut, 2008), and better group thinking (Wood et al, 1985).…”
Section: Prior Research On Gender Diversity In the Boardroom And Kamentioning
confidence: 99%
“…Leader roles in groups that deal with interpersonally demanding tasks should incorporate social skills and thus present less incongruity with the female gender role. In general, women's positive social contributions become more relevant to leadership for tasks requiring negotiation and extensive sharing of ideas (W. Wood, 1987;W. Wood, Polek, & Aiken, 1985), allowing women more opportunity to achieve leadership.…”
Section: Studies Of the Emergence Of Leadersmentioning
confidence: 99%